Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.5392/jkca.2013.13.09.130
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of CB Policy in Korea and Community Business Policy in Japan

Abstract: The objective of the present study was to analyze the functions and requirements of CB (community business) centering on the activation of localities based on research and cases in Japan where CB is discussed actively, and to suggest the necessity and plans for introducing CB in Korea. That is, we examined the utilization of CB fittingly for the condition of Korea centering on success factors derived from research and cases in Japan, and attempted to improve the roles of the government and related organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The heartwood of Caesalpinia sappan L. (belonging to the Leguminosae family) is a herbal medicinal product used for improving blood circulation, accelerating hemostasis, removing extravasated blood, relieving pain, and reducing swelling ( 16 ). In particular, C. sappan has been used to treat gynecological symptoms, including dysmenorrhea and amenorrhea ( 17 , 18 ). Several studies have already shown that C. sappan causes apoptosis of several cancer cell lines ( 19-22 ).…”
Section: Introductionmentioning
confidence: 99%
“…The heartwood of Caesalpinia sappan L. (belonging to the Leguminosae family) is a herbal medicinal product used for improving blood circulation, accelerating hemostasis, removing extravasated blood, relieving pain, and reducing swelling ( 16 ). In particular, C. sappan has been used to treat gynecological symptoms, including dysmenorrhea and amenorrhea ( 17 , 18 ). Several studies have already shown that C. sappan causes apoptosis of several cancer cell lines ( 19-22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ginger ( Zingiber officinals Roscoe) is a rhizome plant that grows in tropical and subtropical countries such as Egypt and Iraq. As a spice of commerce and a perennial herb, ginger has a distinctive spicy flavor and taste properties ( 1 – 3 ). Ginger is used as fresh (green ginger), dried, oleoresin and an essential oil in cooking, and medicinal or cosmetic products ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…공시 재료는 국내에서 식재되고 있는 억새(Miscanthus sinensis) 품종 중에서 7종을 선정하였다(Table 1). 일반적인 특성은 미 농무성(United States Department of Agriculture, USDA)의 Natural Resources Conservation Service Plant Database와 Missouri Botanical Garden (MBG)의 Plant Finder, The Encyclopedia of Grasses for the Livable Landscapes, 산림청(Korea Forest Service, KFS)의 한 국식물 도해도감 및 원색 대한식물도감을 인용하였다 [18,19]. 식물명은 국립수목원(Korea National Arboretum, KNA) 국가표준식물목록(Korean Plant Names Index, KPNI)에 명시된 학명과 품종명을 표기하였고 [21] Horizontal bands of yellow variegation.…”
Section: 공시 재료unclassified